Overview of Induction Drug Dosage Types with the ERACS (Enhanced Recovery After Caesarean Surgery) Sectio Caesarean Method in Post Sectio Caesarean Patients at Hermina General - Ayu Kartika Sari, Venna; Suandika, Made; Burhan, Asmat; Tri Yudono, Danang (Java Nursing Journal, 2024)
The caesarean section method is recognized recently with the concept of ERACS (Enhanced Recovery After Cesarean Surgery). The surgery process is more convenient because there is less pain and the postoperative recovery process is faster than the traditional method. The ERACS concept was developed from the ERAS (Enhanced Recovery After Surgery) concept and applied to gastrointestinal surgery. It has been shown to minimize hospital admissions and complications after surgery, which results in improved patient satisfaction. The design of this study was quantitative non- experimental using descriptive methods conducted in September 2023 with a population of all adult patients undergoing surgery under general anesthesia and a sample of 70 respondents. This method is used to study populations by collecting data to clarify and test hypotheses. This study focuses on describing the types and induction drugs with the ERACS method. in post-cesarean section patients at Hermina General Hospital Yogyakarta. Data were collected using observation techniques recorded in the observation sheet and then analyzed using the frequency distribution test using SPSS version 23. The results showed that most of the respondents in this study were women aged 26-35 years as many as 38 respondents (54.3%). Based on other respondent characteristics, it was also found that the results of blood pressure <130 and <90 mmHg were (52.9%), which is 37 respondents, followed by a pulse of 80-100x/min as many as 40 respondents (57.1%), spo2> 95% as many as 65 respondents (92.9%) ASA 1 as many as 46 respondents (65.7%), and the average use of morphine and fentanyl was (100%) using a combination of morphine drugs with a dose of 0.1mg and fentanyl with a drug dose of 25mcg. Keywords: ERACS, Maternity, Post-Cesarean Section